Fertility-sparing surgery in primary peritoneal serous borderline tumor: a case report - Li, Tingting; Jiang, Wei; Wang, Hongjing (Frontiers in Oncology, 2025)
Primary peritoneal serous borderline tumor (PPSBT) is a rare, low-malignant-potential neoplasm arising from the peritoneum, diagnosed only after excluding ovarian involvement. While typically discovered incidentally during surgery, it often presents with infertility or abdominal pain in young women. Due to its favorable prognosis and the desire to preserve fertility, fertility-sparing surgery (FSS) is a critical consideration. We report a case of PPSBT in a reproductive-aged woman who underwent three FSS procedures, demonstrating the feasibility of this approach. Our findings support FSS as a viable option for PPSBT patients after thorough exclusion of ovarian malignancy. This case underscores the importance of comprehensive surgical staging and multidisciplinary evaluation to optimize oncological and reproductive outcomes. Further research is needed to standardize management strategies for this rare condition.